PEMANFATAN LIMBAH RAMBUT JAGUNG BAKAR (Zea Mays L. sacharata) SEBAGAI KRIM ANTIOKSIDAN DAN TABIR SURYA - Sony Andika Saputra; Munifatul Lailiyah (Fakultas Farmasi UMI, 2020)
Continuous sun exposure to the skin will cause skin damage due to the oxidative effects of free radicals. Phenolic compounds in the form of antioxidants can act as sunscreens to prevent adverse effects due to UV radiation. Positive corn silk contains phenols and flavonoids, which are compounds that have the potential to act as sunscreens and anti-oxidants. This research method was carried out by collecting roasted corn hair waste samples to be made dry simplicia, then extraction extraction with 70% ethanol solvent. The extract obtained was then formulated into a cream with a concentration variation of 1, 5 and 10%. Furthermore, an evaluation of the physical quality of the cream preparation and antioxidant activity test using the DPPH method were also tested for the SPF value. The results showed that the evaluation of the quality of the cream preparations met the requirements. The antioxidant activity test of cream preparations is categorized as very weak. Test the SPF value of cream preparations including the maximum protection category in formulation III.